Public Talks and Science Listens: A Community-Based Participatory Approach to Characterizing Environmental Health Risk Perceptions and Assessing Recovery Needs in the Wake of Hurricanes Katrina and Rita - J. Sullivan; B. Parras; R. St. Marie; W. Subra; S. Petronella; J. Gorenstein; R. Fuchs-Young; R.K. Santa; A. Chavarria; J. Ward; P. Diamond (SAGE Publishing, 2009)
In response to the human health threats stemming from Hurricanes Katrina and Rita, inter-disciplinary working groups representing P30-funded Centers of the National Institute Environmental Health Sciences were created to assess threats posed by mold, harmful alga blooms, chemical toxicants, and various infectious agents at selected sites throughout the hurricane impact zone. Because of proximity to impacted areas, UTMB NIEHS Center in Environmental Toxicology was charged with coordinating direct community outreach efforts, primarily in south Louisiana. In early October 2005, UTMB/NIEHS Center Community Outreach and Education Core, in collaboration with outreach counterparts at The University of Texas MD Anderson Cancer Center @ Smithville TX/Center for Research in Environmental Disease sent two groups into southern Louisiana. One group used Lafourche Parish as a base to deliver humanitarian aid and assess local needs for additional supplies during local recovery/reclamation. A second group, ranging through New Iberia, New Orleans, Chalmette, rural Terrebonne, Lafourche and Jefferson Parishes and Baton Rouge met with community environmental leaders, emergency personnel and local citizens to 1) sample public risk perceptions, 2) evaluate the scope and reach of ongoing risk communication efforts, and 3) determine how the NIEHS could best collaborate with local groups in environmental health research and local capacity building efforts. This scoping survey identified specific information gaps limiting efficacy of risk communication, produced a community "wish list" of potential collaborative research projects. The project provided useful heuristics for disaster response and management planning and a platform for future collaborative efforts in environmental health assessment and risk communication with local advocacy groups in south Terrebonne-Lafourche parishes.